Inadequate water intake of breastfeeding women - Kresic, Greta; Dujmović, Mihela; Mrduljas, Nikolina (Progress in Nutrition, 2016)
Summary. Despite evidence of importance of water for the general population’ health, water intake estimates in breastfeeding women are lacking. Therefore, this study aimed at estimating water intakes and identifying dietary water sources in a sample of Croatian breastfeeding women one month postpartum. For the sake of comparison, water intakes of similarly aged non-breastfeeding postpartum women were estimated too. A total of 83 full-breastfeeding and 76 non-breastfeeding women were recruited. Data on total water intake were collected from two consecutive 24-hour dietary recalls. On average, the breastfeeding women take 73.61% and the non-breastfeeding 88.45% of the recommended water amount. In the breastfeeding women, 44.80% of the total water intake was represented by plain water, 20.02% by other beverages and 35.18% by food moisture, similar as with the non-breastfeeding group (39.40%, 28.30% and 32.30%, respectively). Except for the plain water, whose average intake was 890.32 ml/day in the breastfeeding and 696.24 ml/day in the non-breastfeeding women, the main water sources in the breastfeeding group were milk and dairy, while in the non-breastfeeding group these were sugar-sweetened beverages and vegetables. In the breastfeeding group, water intake positively correlated with the total (r=0.47; p